Impact of prehospital transfer strategies in major trauma and head injury: Systematic review, meta-analysis, and recommendations for study design. Issue 1 (January 2015) - Pickering, Alastair; Cooper, Katy; Harnan, Susan; Sutton, Anthea; Mason, Suzanne; Nicholl, Jonathan
Abstract : BACKGROUND: It is unclear whether trauma patients should be transferred initially to a trauma center or local hospital. METHODS: A systematic review and meta-analysis assessed the evidence for direct transport to specialist centers (SCs) versus initial stabilization at non-SCs (NSCs) for major trauma or moderate-to-severe head injury. Nine databases were searched from 1988 to 2012. Limitations in the study design informed recommendations for future studies. RESULTS: Of 19 major trauma studies, five (n = 19, 910) included patients not transferred to SCs and adjusted for case mix. Meta-analysis showed no difference in mortality for initial triage to NSCs versus SCs (odds ratio [OR] 1.03; 95% confidence interval [CI], 0.85–1.23). Within studies excluding patients not transferred to SCs, unadjusted analyses of mortality nonsignificantly favored transfer via NSCs (16 studies; n = 37, 079; OR, 0.83; 95% CI, 0.68–1.01), whereas adjusted analysis nonsignificantly favored direct triage to SCs (9 studies; n = 34, 266; OR, 1.18; 95% CI, 0.96–1.44). Of 11 head injury studies, all excluded patients not transferred to SCs and half were in remote locations. There was no significant mortality difference between initial triage to NSCs versus SCs within adjusted analyses (3 studies; n = 1, 507; OR, 0.74; 95% CI, 0.31–1.79) or unadjusted analyses (10 studies; n = 3, 671; OR, 0.87; 95% CI, 0.62–1.23). CONCLUSION: This systematic review demonstrated no difference in outcomes for direct transport to a trauma center versus initial triage to a local hospital. Many studies had significant limitations in the design, and heterogeneity was high. Recommendations for future studies include the following: (i) inclusion of patients not transferred to SCs and those dying during transport; (ii) clear description of centers plus transport distances/times; (iii) adjustments for case mix; and (iv) assessment of morbidity and mortality. LEVEL OF EVIDENCE: Systematic review, level IV. Abstract : Supplemental digital content is available in the text.